2015
DOI: 10.6007/ijarbss/v5-i10/1860
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Structuring Employability Skills for Accounting Students

Abstract: The development of soft and technical skills as part of tertiary education courses is key to enhancing the employability skills of graduating students. Within the accounting profession there is little agreement over which skills should be developed and a wide range have been suggested as relevant. A sample (n = 62) of higher education educators and industry practitioners were surveyed to elicit their assessments of the importance of a range of employability skills. Exploratory Factor Analysis was used to group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…The top five generic skills group most frequently requested in the job advertisements is: communication skills (26.2%), self-management skills (19.4%), teamwork skills (16.2%), creativity and innovation skills (12.0%), problem-solving skills (11.5%). The study's findings are in line with previous studies (Singh, et al, 2013;Olawale, 2015;Warwick & Howard, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The top five generic skills group most frequently requested in the job advertisements is: communication skills (26.2%), self-management skills (19.4%), teamwork skills (16.2%), creativity and innovation skills (12.0%), problem-solving skills (11.5%). The study's findings are in line with previous studies (Singh, et al, 2013;Olawale, 2015;Warwick & Howard, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Closely followed by interpersonal and team work skills. Previously, Warwick & Howard (2015) also found the communication skills, analytical skills, problem solving, interpersonal skills, teamwork, self-management, and critical analysis as a high ranking skills required by accounting graduates in entering the world of work.…”
Section: The Employers' Demands On Employability Skillsmentioning
confidence: 95%
“…In their comprehensive study, Jackling and De Lange ( 2009) identified a range of important skills that business graduates need to be successful in employment and in their future career. In a more recent note, Warwick and Howard (2015) provide a comprehensive skills list from the employers' perspectives, which includes skills in business case analysis techniques (such as sound knowledge of the forecasting of business data using web-based applications). Discipline-specific technical skills are also important for graduates' employability.…”
Section: Technical Skills (Ts)mentioning
confidence: 99%
“…Prior studies argue that technical skills are inadequate for job success in the areas of business and management (Jackling and De Lange, 2009;Hirsch and Collins, 1988). A growing number of studies argue that soft skills are complementary to technical skills, with both required for graduate employment (Mohamed and Lashine, 2003;Warwick and Howard, 2015). Soft skills include communication skills, interpersonal skills and behavioural skills, as demonstrated through teamwork and leadership (Teng et al, 2019).…”
Section: Soft Skills (Ss)mentioning
confidence: 99%
See 1 more Smart Citation